Comparison of the corrosion behavior and surface morphology of NiTi alloy and stainless steels in sodium chloride solution - Kožuh, Stjepan; Vrsalović, Ladislav; Gojić, Mirko; Gudić, Senka; Kosec, Borut (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
The corrosion behavior of NiTi alloy and stainless steels (AISI 316L and X2CrNiMoN22-5-3) in 0.9% sodium chloride (0.154 moll-1) solution was investigated using open circuit potential measurements, potentiodynamic polarization and electrochemical impedance spectroscopy measurements. Microstructural analyses before and after electrochemical tests were performed with the scanning electron microscopy (SEM) equipped with energy dispersive spectrometry (EDS). The lowest corrosion current density has NiTi alloy and the extent of the passive range increased in the order AISI 316L stainless steel < NiTi alloy < X2CrNiMoN22-5-3 duplex stainless steel. The oxide film formed on all samples has a double-layer structure consisting of a barrier-type inner layer and a porous outer layer. Oxide films formed on the surface of steels mainly contains iron oxides and chromium oxide, while the surface film of the NiTi alloy mainly contains TiO2 oxide.